2018
DOI: 10.1111/bjc.12178
|View full text |Cite
|
Sign up to set email alerts
|

Clinician‐rated and self‐reported psychotic‐like experiences in individuals accessing a specialist Youth Mental Health Service

Abstract: Clinical Implications Psychotic-like experiences are common in young people with severe non-psychotic mental health problems and should be routinely screened in mental health services. Psychotic-like experiences were found to be more prevalent when using a self-report screening tool compared to a clinician-rated measure. The presence of psychotic-like experiences may reflect more severe and complex mental health problems and may also cause delays in young people accessing the right kind of support. ;Limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
2
6
1
Order By: Relevance
“…For example, mobile technology-based activity measures using actigraphy and measures of negative symptoms through video may provide more objective measures. Our findings support recommendation by others on using multiple sources of information for assessing personality (Dinger et al, 2013;McDonald, 2008) and psychotic-like experiences (Hodgekins et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, mobile technology-based activity measures using actigraphy and measures of negative symptoms through video may provide more objective measures. Our findings support recommendation by others on using multiple sources of information for assessing personality (Dinger et al, 2013;McDonald, 2008) and psychotic-like experiences (Hodgekins et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…In two studies that examined relatives of patients with schizophrenia, self-report measures of schizotypy performed worse than clinical interviews at identifying relatives of patients with schizophrenia, suggesting that questionnaires are less successful at assessing underlying vulnerability for schizophrenia (Kendler et al, 1996(Kendler et al, , 1993. Self-report questionnaires assessing psychotic-like experiences greatly overestimate the prevalence of psychosis and attenuated positive symptoms when compared with clinician ratings on the same individuals using a clinical interview (Schultze-Lutter et al, 2014) or checklists (Hodgekins et al, 2018). Spitz et al (2017) reported low correlations between self-and observer-rated positive, negative, and affective symptoms in at-risk mental state and first-episode psychosis patients.…”
Section: Introductionmentioning
confidence: 95%
“…Further, the prevalence of at-risk mental states was more substantial than both full-threshold and subthreshold bipolar and psychotic diagnoses, suggesting that such features are common in those presenting to youth mental health services, occurring much more frequently than overt psychotic or bipolar disorders. The prevalence of psychosis-like experiences in this sample is higher than the 6%–12% reported in adults and adolescents in the general population67–69 but lower than previous reports in young people presenting for mental healthcare, which have found prevalence closer to 50% even in non-psychotic samples 70 71. The more conservative prevalence in the current study is likely due to the method of data collection, as less severe psychosis-like symptoms may not have been specifically assessed or recorded by clinicians.…”
Section: Findings To Datecontrasting
confidence: 79%
“…This also holds for clinical samples. A study conducted on 108 adolescent outpatients (12–16 years) showed that 78% of those who reported PLEs also met the criteria for two or more non-psychotic psychiatric disorders [11] and the presence of PLEs were associated with poorer social and role functioning and increased severity of non-psychotic symptoms [1416]. The occurrence of PLEs in adolescents seems closely linked to various psychiatric symptoms [12, 13, 1719].…”
Section: Introductionmentioning
confidence: 99%